Integration of theoretical principals of psychosomatic medicine and practice of Balint supervision in physicians in the promotion of effective professional communication - V A Vinokur; T A Karavaeva (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The review of the Russian and foreign literature on the relationships of psychosomatic medicine and Balint supervision of physicians was conducted. We selected and analyzed articles from MEDLINE / PubMed Elibrary.ru, Scopus databases during from 1990 till 2020, international medical journals and collections of scientific papers as well as relevant references in the bibliography of the analyzed articles. The search was carried out with the usage of search queries of various combinations of the specified key words.The “philosophy” of psychosomatic medicine and the theory of Balint supervision have the evident common historical grounds. Psychosomatic medicine and Balint supervision are united by the conception that the patient’s perceptions about his/her illness, related to it experiences and behavior as well as their relationships to his/her unconscious are very important in the therapy process. That means that the experiences and behavior of a physician related to the complicated communication with the patient are important as well. The patient has to be no more a passive object of the care so the process of therapy obtains the character of interpersonal communication and the mutual influence between the patient and the physician. This point is what Balint supervision is focused at. The technology of Balint group work helps physicians to shift an emphasis in the clinical practice from the disease-centered to the patient-centered approach. The analysis of Balint groups effectiveness provided during more than fifty years brought an evidence that Michael Balint presented very efficient method which helped physicians in different medical fields and psychologists reduce their emotional arousal in the treatment of “difficult” patients who are patients with psychosomatic disorders very frequently. The integrative relationships between basic approaches of psychosomatic medicine and Balint supervision in physicians and psychologists are described. The history of the relations and common principles related to the attention to the complexed issues of physician-patient communication and the therapy in psychosomatic disorders which becomes more successful due to the impact of analytical Balint supervision, are analyzed. The significance of Balint groups work in the training of the health care professionals, who are treating patients with psychosomatic disorders, difficulties and perspectives of implementation of Balint group method into the system of education and training of general practitioners, psychiatrists and psychotherapists are presented.